Strategies to Cope With the COVID-Related Deaths Among Family Members - Borghi, Lidia; Menichetti, Julia (Frontiers in Psychiatry, 2021)
The extraordinary circumstances of deaths during COVID-19 pandemic have been challenging for the deceased’s families. This contribution aims to describe some spontaneous strategies that family members may adopt to cope with the loss of a relative for COVID-19. The present reflection derives from the experience of a clinical psychology unit of one of the biggest public hospital in Milan, Italy, which supported 246 families of COVID-19 victims in the first days after the loss. Spontaneous strategies used by family members to deal with such a unique mourning process involved: creating alternative good-bye rituals, normalizing the loss, addressing faith and hope, highlighting the perks of isolation, supporting others in need, and delivering the bad news to others. These observed strategies may suggest how to assess and support a ‘normal’ bereavement process during the extraordinary COVID-19 circumstances, in order to prevent further psychological distress.